Dynamic risk modeling for safe car parking in climbing over urban curbs - Yakut, Oğuz; Eren, Haluk; Kaya, Mustafa; Öksüztepe, Eyyüp; Polat, Mehmet; Omaç, Zeki; Bekler, Derya; Kürüm, Hasan; Çelenk, Mehmet (My University, 2013)
In urban areas, safe and secure vehicle parking presents various problems as vehicles are driven at low speeds toward available parking spots. If there is an obstacle in front or back of the car, drivers have to accelerates their cars from zero to higher speed to pass over the obstruction. Obstacle could be curbs, bumper or any rim over the parking area. In this case, we assume the obstacle to be a curb. Therefore, driver has to get over the obstacle by stepping on the gas of his car. This action can result in hazardous situation to the car, pedestrians or obstacles around the car. In the proposed system, we estimate jumping distance of the car considering major components attributing to scenario. As outcomes, we have obtained the balance between the car performance and steep level of the curb. This would be a guidance not only designing urban areas but also estimating dynamic behavior of the car after detecting the obstacle profile.
Bildiri - Yayımlanmamış
Keywords: Safe parking; Curbs; Low speed accident; Obstacle models; Car torque